Expression of ALS/FTD-linked mutant CCNF in zebrafish leads to increased cell death in the spinal cord and an aberrant motor phenotype. (21st April 2017) - Hogan, Alison L; Don, Emily K; Rayner, Stephanie L; Lee, Albert; Laird, Angela S; Watchon, Maxinne; Winnick, Claire; Tarr, Ingrid S; Morsch, Marco; Fifita, Jennifer A; Gwee, Serene S L; Formella, Isabel; et al.
Abstract: Amyotrophic lateral sclerosis (ALS) is a rapidly progressive, fatal neurodegenerative disease characterised by the death of upper and lower motor neurons. Approximately 10% of cases have a known family history of ALS and disease-linked mutations in multiple genes have been identified. ALS-linked mutations in CCNF were recently reported, however the pathogenic mechanisms associated with these mutations are yet to be established. To investigate possible disease mechanisms, we developed in vitro and in vivo models based on an ALS-linked missense mutation in CCNF . Proteomic analysis of the in vitro models identified the disruption of several cellular pathways in the mutant model, including caspase-3 mediated cell death. Transient overexpression of human CCNF in zebrafish embryos supported this finding, with fish expressing the mutant protein found to have increased levels of cleaved (activated) caspase-3 and increased cell death in the spinal cord. The mutant CCNF fish also developed a motor neuron axonopathy consisting of shortened primary motor axons and increased frequency of aberrant axonal branching. Importantly, we demonstrated a significant correlation between the severity of the CCNF -induced axonopathy and a reduced motor response to a light stimulus (photomotor response). This is the first report of an ALS-linked CCNF mutation in vivo and taken together with the in vitro model identifies the disruption of cell death pathways as a significant consequence of this mutation. Additionally, this study presents a valuable new tool for use in ongoing studies investigating the pathobiology of ALS-linked CCNF mutations.